Предмет: Алгебра, автор: veronikamukhortova15

помогити с заданием пожалуйста ​

Приложения:

Ответы

Автор ответа: hedggehog
1

 \frac{x - 2b}{ {x}^{2} - 2bx }  =   \frac{x - 2b}{x(x - 2b)}  =  \frac{1}{x}

 \frac{3x + a}{ {(x + a)}^{2} }  +  \frac{x + 3a}{ {(x + a)}^{2} }  =  \frac{3x + a + x + 3a}{ {(x + a)}^{2} } =   \frac{4x + 4a}{(x + a) {}^{2} }  =  \frac{4(x + a)}{ {(x + a)}^{2} }  =  \frac{4}{x + a}

 \frac{3x}{y}  -  \frac{x}{y}  =  \frac{3x - x}{y}  =  \frac{2x}{y}

 \frac{1}{ {a}^{2}  }  +  \frac{a - 2}{a}  =  \frac{1 + a(a - 2)}{ {a}^{2} }  =  \frac{1 +  {a}^{2}  - 2a}{ {a}^{2} }  =  \frac{(a - 1) {}^{2}  }{ {a}^{2} }

Похожие вопросы
Предмет: Русский язык, автор: karinka2287